Study on Intelligent Recommendation Method of Dueling Network Reinforcement Learning Based on Regret Exploration - HONG Zhi-li, LAI Jun, CAO Lei, CHEN Xi-liang, XU Zhi-xiong (Jisuanji kexue, 2022)
In recent years,the application of deep reinforcement learning in recommendation system has attracted much attention.Based on the existing research,this paper proposes a new recommendation model RP-Dueling,which is based on the deep reinforcement learning Dueling-DQN algorithm,and adds the regret exploration mechanism to make the algorithm adaptively and dynamically adjust the proportion of “exploration-utilization” according to the training degree.The algorithm can capture users’ dynamic interest and fully explore the action space in the recommendation system with large-scale state space.By testing the proposed algorithm model on multiple data sets,the optimal average results of MAE and RMSE are 0.16 and 0.43 respectively,which are 0.48 and 0.56 higher than the current optimal research results.Experimental results show that the proposed model is superior to the existing traditional recommendation model and recommendation model based on deep reinforcement learning.